Wednesday

October 22, 2014

October 22, 2014

Posted by **BL** on Tuesday, May 13, 2014 at 10:47pm.

g(X)2X-5

(Fog)(X)F(g(x))

3 (2X-5)-5X+1

6X-15-5X+1

2(3Xsquared-5X+1)-5

6Xsquared-10X+2-5

6Xsquared-10X-3

- Intermediate Algebra -
**Steve**, Tuesday, May 13, 2014 at 11:49pmf(x) = 3x^2-5x+1

g(x) = 2x-5

(fog)(x) = f(g) = 3g^2-5g+1

= 3(2x-5)^2 - 5(2x-5) + 1

= 3(4x^2-20x+25) - 5(2x-5) + 1

= 12x^2-60x+75-10x+25+1

= 12x^2-70x+101

Looks like you messed up on the -5(2x-5) part

**Answer this Question**

**Related Questions**

Algebra - There is a table of values for the function f. They read: x=3, f(x)=4 ...

algebra - Solve for s in this equation. Depreciation. D=C-s/n This is my answer ...

algebra - could you please multiply these together and tell me what you come up ...

8th Grade Algebra: Answer Check #2 - Add or Subtract (Radicals) { this means ...

General - Please understand that I am not upset with anyone or whatever I just ...

8th Grade Algebra: Answer Check - Find the length of the 3rd side of each right ...

Algebra - Hiya. I have 7 expressions that I have been asked to simplify. I ...

Algebra - Need help finding composition of functions. I am doing something wrong...

College Math - Nick received a $7000.00 raise. If his previous salary was 55000....

MATH - PLEASE HELP! - Need help with combining like terms How do I figure this ...